evaluate the integral tan inverse √X dx
Answers
Answered by
50
Hey there!
Solution :
Let this be the equation ( a )
Put
= t
x =![t^{2} t^{2}](https://tex.z-dn.net/?f=t%5E%7B2%7D)
Now differentiate both sides wrt x ;
dx = 2t .dt
Substituting the value of t and dx in eq. ( a )
Now Integration by parts ;
![I = 2 ( tan^{-1} \int ( t .dt ) - \int ( \dfrac{d ( tan^{-1} t )}{dx} . \int ( t . dt ) ) dt\\ \\ I = 2 ( tan^{-1} t . \dfrac{t^{2}}{2} - \int ( \dfrac{1}{1 + t^{2}} . \dfrac{t^{2}}{2} ) dt\\ \\ I = 2 ( \dfrac{t^{2}}{2} tan^{-1} t - \dfrac{2}{2} \int \dfrac{t^{2}}{ 1 + t^{2}}. dt\\ \\ I = t^{2} tan^{-1} t - 1 \int \dfrac{( t^{2} + 1 ) - 1}{1 + t^{2}} .dt\\ \\ I = t^{2} tan^{-1} t - \int ( dt ) - \int ( \dfrac{1}{1 + t^{2}}. dt ) \\ \\ I = t^{2} tan^{-1} t - ( t - tan^{-1} t ) \\ \\I = t^{2} tan^{-1} t - t + tan^{-1} t + c I = 2 ( tan^{-1} \int ( t .dt ) - \int ( \dfrac{d ( tan^{-1} t )}{dx} . \int ( t . dt ) ) dt\\ \\ I = 2 ( tan^{-1} t . \dfrac{t^{2}}{2} - \int ( \dfrac{1}{1 + t^{2}} . \dfrac{t^{2}}{2} ) dt\\ \\ I = 2 ( \dfrac{t^{2}}{2} tan^{-1} t - \dfrac{2}{2} \int \dfrac{t^{2}}{ 1 + t^{2}}. dt\\ \\ I = t^{2} tan^{-1} t - 1 \int \dfrac{( t^{2} + 1 ) - 1}{1 + t^{2}} .dt\\ \\ I = t^{2} tan^{-1} t - \int ( dt ) - \int ( \dfrac{1}{1 + t^{2}}. dt ) \\ \\ I = t^{2} tan^{-1} t - ( t - tan^{-1} t ) \\ \\I = t^{2} tan^{-1} t - t + tan^{-1} t + c](https://tex.z-dn.net/?f=+I+%3D+2+%28+tan%5E%7B-1%7D+%5Cint+%28+t+.dt+%29+-+%5Cint+%28+%5Cdfrac%7Bd+%28+tan%5E%7B-1%7D+t+%29%7D%7Bdx%7D+.+%5Cint+%28+t+.+dt+%29+%29+dt%5C%5C+%5C%5C+I+%3D+2+%28+tan%5E%7B-1%7D+t+.+%5Cdfrac%7Bt%5E%7B2%7D%7D%7B2%7D+-+%5Cint+%28+%5Cdfrac%7B1%7D%7B1+%2B+t%5E%7B2%7D%7D+.+%5Cdfrac%7Bt%5E%7B2%7D%7D%7B2%7D+%29+dt%5C%5C+%5C%5C+I+%3D+2+%28+%5Cdfrac%7Bt%5E%7B2%7D%7D%7B2%7D+tan%5E%7B-1%7D+t+-+%5Cdfrac%7B2%7D%7B2%7D+%5Cint+%5Cdfrac%7Bt%5E%7B2%7D%7D%7B+1+%2B+t%5E%7B2%7D%7D.+dt%5C%5C+%5C%5C+I+%3D+t%5E%7B2%7D+tan%5E%7B-1%7D+t+-+1+%5Cint+%5Cdfrac%7B%28+t%5E%7B2%7D+%2B+1+%29+-+1%7D%7B1+%2B+t%5E%7B2%7D%7D+.dt%5C%5C+%5C%5C+I+%3D+t%5E%7B2%7D+tan%5E%7B-1%7D+t+-+%5Cint+%28+dt+%29+-+%5Cint+%28+%5Cdfrac%7B1%7D%7B1+%2B+t%5E%7B2%7D%7D.+dt+%29+%5C%5C+%5C%5C+I+%3D+t%5E%7B2%7D+tan%5E%7B-1%7D+t+-+%28++t+-+tan%5E%7B-1%7D+t+%29+%5C%5C+%5C%5CI+%3D+t%5E%7B2%7D+tan%5E%7B-1%7D+t+-+t+%2B+tan%5E%7B-1%7D+t+%2B+c)
Now substitute the value of t ;
![I = x tan^{-1} \sqrt{x} - \sqrt{x} + tan^{-1} \sqrt{x} + c \\ \\ I = tan^{-1} \sqrt{x} ( x + 1 ) - \sqrt{x} + c I = x tan^{-1} \sqrt{x} - \sqrt{x} + tan^{-1} \sqrt{x} + c \\ \\ I = tan^{-1} \sqrt{x} ( x + 1 ) - \sqrt{x} + c](https://tex.z-dn.net/?f=I+%3D+x+tan%5E%7B-1%7D+%5Csqrt%7Bx%7D+-+%5Csqrt%7Bx%7D+%2B+tan%5E%7B-1%7D+%5Csqrt%7Bx%7D+%2B+c+%5C%5C+%5C%5C+I+%3D+tan%5E%7B-1%7D+%5Csqrt%7Bx%7D+%28+x+%2B+1+%29+-+%5Csqrt%7Bx%7D+%2B+c)
#BeBrainly.
Solution :
Let this be the equation ( a )
Put
x =
Now differentiate both sides wrt x ;
dx = 2t .dt
Substituting the value of t and dx in eq. ( a )
Now Integration by parts ;
Now substitute the value of t ;
#BeBrainly.
darshita93:
what problem u have from me... you have deleted 2 questions of mine why can u explain mee..
Similar questions